The international law of sovereign debt dispute settlement / Kei Nakajima, The University of Tokyo. - Nakajima, Kei, 1983- (Cambridge studies in international and comparative law (Cambridge, England : 1996), 2022)
The first two decades of the twenty-first century witnessed a series of large-scale sovereign defaults and debt restructurings, in which sovereigns struggled to negotiate with recalcitrant bondholders, particularly hedge funds. Also, the outbreak of the COVID-19 pandemic in 2020 heralded a bleak financial outlook for many developing and emerging market countries, requiring sovereign debt restructuring in times of great macroeconomic uncertainty. Given the absence of a multilateral mechanism for sovereign debt restructuring equivalent to domestic corporate bankruptcy system, however, defaulted sovereigns often suffer from holdout litigation wrought by bondholders. This book proposes ways in which such legal actions could be regulated without the undue expense of bondholders' remedies by exploring the mechanism of balancing bondholder protection and respect for sovereign debt restructuring at various stages of litigation and arbitration proceedings.